Relasi Struktur Pemerintahan Sipil dan Mantan Kombatan Militer GAM Dalam Pengambilan Kebijakan Pemerintah Pasca MoU Helsinki - egi gunawan; Ubaidullah MA (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRAK, Penelitian ini berjudul “Relasi Struktur Pemerintahan Sipil dan Mantan Kombatan Militer GAM Dalam Pengambilan Kebijakan Pemerintah Pasca MoU Helsinki”. Pejuang GAM yang saat ini mengemban amanat rakyat dapat dijadikan sebagai simbol dari harapan-harapan rakyat Aceh dalam menggapai kehidupan yang layak tanpa adanya kemiskinan dan pengangguran pasca konflik. Tujuan penelitian ini adalah untuk menjawab dan mengkaji relasi pengambilan kebijakan pemerintah pasca MoU Helsinki antara pemerintahan sipil dan mantan kombatan militer GAM. Teori yang digunakan adalah Teori Strukturasi dan Teori Kebijakan, dimana melihat mantan kombatan GAM pasca MoU Helsinki dilihat dari dualitas struktur dan memperoleh tujuan yang sama dalam mewujudkan kesejahteraan rakyat Aceh melalui kebijakan pemerintah. Metode penelitian ini menggunakan teknik analisis data kualitatif dengan jenis penelitian deskriptif. Alat pengumpulan data pada penelitian ini berupa wawancara semi struktur dan studi dokumentasi.  Teknik pemilihan informan yang digunakan dalam penelitian ini adalah teknik purposif. Berdasarkan hasil pengolahan data secara interaktif. Adapun temuan dalam penelitian ini adalah relasi struktur pemerintahan sipil dan mantan kombatan militer GAM dalam pengambilan kebijakan pemerintah pasca MoU Helsinki dalam perjalanannya tidak semudah apa yang dicita-citakan, dana reintegrasi tidak dimasukkan dalam agenda kebijakan pemerintah Aceh serta terjadi ketidakharmonisan antara para elit mantan kombatan militer GAM yang sedang duduk di Pemerintahan Aceh maupun yang sudah tidak lagi menjabat, hal ini merupakan salah satu penghambat dalam implementasi kebijakan pemerintah dan menghambat memaksimalkan sektor-sektor unggulan untuk mewujudkan kesejahteraan rakyat Aceh. RELATIONSHIP OF THE STRUCTURE OF CIVIL GOVERNMENT AND MILITARY EX-COMBATANT GAM IN GOVERNMENT POLICY MAKING POST HELSINKI MOU ABSTRACT, This study entitled "Relationship of The Structure of Civil Government and Military Ex-Combatant GAM in Government Policy Making Post Helsinki MoU". GAM is an armed political movement that was born and grew in Aceh. Since the declaration of GAM on 4 December 1976 lists in Pidie by Teungku Hasan Muhammad di Tiro, the armed political movement continued to be morphed into an armed resistance movement to demand independence from the unitary State of the Republic of Indonesia over the injustice against the implementation of Central Government policies. GAM fighters are currently carrying out the people's mandate could serve as a symbol of the Aceh people's expectations in reaching a decent life without poverty and unemployment in post conflict. The purpose of this research is to know and to examine relationships in a post-war Government for making the Helsinki MoU between the structure of civilian Government and military ex-combatant GAM. The theory of Structuration Theory is Theory and policy, which saw military ex-combatant GAM post Helsinki MoU is seen from the duality structure and obtain the same objective in realizing the welfare of the people of Aceh through government policy. The method of this research uses qualitative data analysis techniques with the kind of descriptive research. Data collection tools on this research in the form semi-structured interviews and documentation study. The informant selection technique used in this study was purposive technique. Based on the results of data processing interactively. The results of this research that on relationship of the structure of civilian Government and military ex-combatant GAM for making government policy post Helsinki MoU to materialize peace and welfare of Acehnese turned out on his journey is not as easy as what imaginable and in reintegration fund, aspire is not included in the Government's policy agenda in Aceh as well as happened the disharmony between the elites military ex-combatant GAM who were sitting in the Aceh Government and have not again, this is one of obstacles in the implementation of government policies and hindered in maximizing leading sectors to realize the Acehnese people’s welfare.